The IgA of hares (Lepus sp.) and rabbit confirms that the leporids IgA explosion is old and reveals a new case of trans-species polymorphism - Pinheiro, Ana; de Sousa-Pereira, Patrícia; Esteves, Pedro J. (Frontiers in Immunology, 2023)
Background Immunoglobulin A (IgA) is the mammalian mucosal antibody, providing an important line of defense against pathogens. With 15 IgA subclasses, the European rabbit has an extremely complex IgA system, strikingly more complex than most other mammals, which have only one IgA or, in the case of hominoids, two IgA subclasses. Similar to the two hominoid primate IGHA genes, the expansion of the rabbit IGHA genes appears to have begun in an ancestral lagomorph since multiple IgA copies were found by Southern blot analysis for the genera Sylvilagus, Lepus, and Ochotona. Results To gain a better insight into the extraordinary lagomorph IgA evolution, we sequenced, for the first time, expressed IgA genes for two Lepus species, L. europaeus and L. granatensis. These were aligned with the 15 rabbit IgA isotypes, and evolutionary analyses were conducted. The obtained phylogenetic tree shows that the Lepus IgA sequences cluster with and among the rabbit IgA isotypes, and the interspecies and intraspecies nucleotide genetic distances are similar. A comparison of the amino acid sequences of the Lepus and rabbit IgA confirms that there are two trans-species polymorphisms and that the rabbit and Lepus sequences share a common genetic pool. In fact, the main differences between the studied leporids IgAs reside in the characteristics of the hinge region. Conclusion The Lepus IgA sequences we have obtained strongly suggest that the great expansion of the leporid IGHA genes occurred in a common ancestral species and was then maintained in the descendants. A strong selective pressure caused the extraordinary expansion of the IGHA genes but then subsided, leading to the maintenance of the acquired polymorphisms in the descendants, with little subsequent divergence. This is a unique evolutionary pattern in which an ancient gene expansion has been maintained for approximately 18 million years.